PREFERENSI SUMBER BELAJAR ONLINE MAHASISWA PENDIDIKAN EKONOMI - Ghofur, Muhammad Abdul; Wahjoedi, Wahjoedi (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2018)
The availability of an increasingly diverse and number of online resources makes the choice of students richer and active learning more enjoyable, but the preferences and abilities of students in choosing the right learning resources need to be further analyzed. This research is survey research with cross-section data with Unesa Economic Education Study Program students as the research subject. The ability of the online student learning resource Preference Unesa is dominated by scientific journal portals, social media, institutional pages, news portals and personal blogs. Most of these learning resources are text rather than the video with ease of access being the main reason in choosing learning resources. Information about the learning resources they get mainly from social media, advice from friends, and then advice or information from lecturers.